2020
DOI: 10.1364/oe.386406
|View full text |Cite
|
Sign up to set email alerts
|

Remote recovery of audio signals from videos of optical speckle patterns: a comparative study of signal recovery algorithms

Abstract: Optical remote sensors are nowadays ubiquitously used, thanks to unprecedented advances in the last decade in photonics, machine learning and signal processing tools. In this work we study experimentally the remote recovery of audio signals from the silent videos of the movement of optical speckle patterns. This technique can be used even when in between the source and the receiver there is a medium that does not allow for the propagation of sound waves. We use a diode laser to generate a speckle pattern on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 17 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…To extract audio signals from optical speckle patterns, the principle signal processing algorithms include cross-correlation, flux variations, optical flow, channel fusion, complex pyramid [13], and machine learning. Barcellona et al compared the commonly used algorithms and concluded that the machine learning method obtained the best performance [14]. However, detailed investigation of machine learning method is not introduced in that paper.…”
Section: Introductionmentioning
confidence: 99%
“…To extract audio signals from optical speckle patterns, the principle signal processing algorithms include cross-correlation, flux variations, optical flow, channel fusion, complex pyramid [13], and machine learning. Barcellona et al compared the commonly used algorithms and concluded that the machine learning method obtained the best performance [14]. However, detailed investigation of machine learning method is not introduced in that paper.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the requirement for sampling human speech is at least 8 kHz. The real time sampling rate of previous methods cannot satisfy this requirement [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…12 Different approaches for extracting meaningful information from speckle patterns have been proposed. [13][14][15] In addition, the intensity distribution, the speckle spot size, and speckle correlations provide information of the spectral properties of the source that generates the light. 16 High-precision spectrometers have been demonstrated, where wavelength-dependent speckle patterns are detected and, after calibration, used to recover the spectrum of the light.…”
Section: Introductionmentioning
confidence: 99%
“…For example, speckle has been used for remote vibration analysis and the remote recovery of audio signals 12 . Different approaches for extracting meaningful infor-arXiv:2006.02719v1 [physics.optics] 4 Jun 2020 mation from speckle patterns have been proposed [13][14][15] .…”
Section: Introductionmentioning
confidence: 99%